Tracing Differential Pathways of Risk: Associations Among Family Adversity, Cortisol, and Cognitive Functioning in Childhood. Issue 4 (17th June 2015) - Suor, Jennifer H.; Sturge‐Apple, Melissa L.; Davies, Patrick T.; Cicchetti, Dante; Manning, Liviah G.
<x xml:space="preserve">Abstract</x> Guided by family risk and allostasis theoretical frameworks, the present study utilized a prospective longitudinal design to examine associations among family risk experiences, basal cortisol patterns, and cognitive functioning in children. The sample included 201 low‐income children living within a midsize city in the Northeastern United States. Children were assessed at ages 2, 3, and 4 years. Growth‐mixture modeling analyses revealed three basal cortisol patterns (elevated, moderate, low) and these remained relatively stable across time. Exposure to greater levels of family instability and maternal unresponsiveness predicted elevated and low cortisol patterns, which were associated with lower child cognitive functioning at age 4. Findings have implications for family risk processes that may underlie risk‐related disparities in child cognitive outcomes.